Pengaruh Program Adiwiyata Terhadap Sikap Peduli Lingkungan Siswa di SMA Negeri 3 Palu - Bungadia, Shinta; Amiruddin (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This research aims at determining the influence of the Adiwiyata program on environmental care attitudes in SMA Negeri 3 Palu. This research used a quantitative method. The research subjects were the grade XI IIS students of SMA Negeri 3 Palu. The data were collected through observation, questionnaires, and documentation. The data were analyzed using the product-moment correlation method and the T-test was used to determine the influence of the Adiwiyata Program on the students. Based on the results of t-test statistical calculations using the Paired t-test formula in which the influence of the Adiwiyata program variable as (X) and the students' environmental care attitude as (Y) show that the value of t-counted is 25.430. So, it is clear that t-tcounted> t-table (25,430> 2,045). Based on the guidelines described in the previous chapter, namely if t-counted> -t-table at the 95% confidence level or α = 0.05, then the hypothesis H0 is rejected and H1 is accepted, so it is proven that the Adiwiyata program (X) gives a significant influence on the students' environmental care (Y). learning, such as smartphone and network coverage.